The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.3892/ijo.2012.1419
|View full text |Cite
|
Sign up to set email alerts
|

17-allylamino-17-demethoxygeldanamycin and ritonavir inhibit renal cancer growth by inhibiting the expression of heat shock factor-1

Abstract: Abstract. Our previous study showed that the combination of a histone deacetylase (HDAC) inhibitor and an HIV protease inhibitor is effective against renal cancer cells. Because HDAC inhibition disrupts the chaperon function of heat shock protein (HSP) 90, we hypothesized that the combination of 17-allylamino-17-demethoxygeldanamycin (17-AAG), an inhibitor of HSP90, and the HIV protease inhibitor ritonavir would also act against renal cancer. The combination of 17-AAG and ritonavir induced apoptosis and inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…We demonstrated an additive effect on cell death in PANC-1 cells, suggesting the benefits of ritonavir as part of combination therapy. Of note, there is a beneficial effect of combining 7-allylamino-17-demethoxygeldanamycin and ritonavir as a novel therapeutic target by inhibiting the expression of heat shock factor-1 in the treatment of renal cancer [18]. …”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated an additive effect on cell death in PANC-1 cells, suggesting the benefits of ritonavir as part of combination therapy. Of note, there is a beneficial effect of combining 7-allylamino-17-demethoxygeldanamycin and ritonavir as a novel therapeutic target by inhibiting the expression of heat shock factor-1 in the treatment of renal cancer [18]. …”
Section: Discussionmentioning
confidence: 99%
“…In the present study, ritonavir itself exhibited antiproliferative activity against renal cancer cells, suggesting that it may not only act as a CYP3A4 inhibitor. Ritonavir was recently shown to exert antitumor effects through the inhibition of proteins such as nuclear factor-κB (14) and heat shock protein (HSP) 90 (15) and it was also reported to inhibit renal cancer growth by inhibiting heat shock factor 1, a transcription factor of HSP 90, when used in combination with 17-allylamino-17-demethoxygeldanamycin (16). Furthermore, the inhibition of HDACs, particularly HDAC6, acetylates HSP 90 and suppresses its function as a molecular chaperone (17).…”
Section: Discussionmentioning
confidence: 99%
“…Small molecule inhibitors of the chaperone HSP90 are a growing class of clinically utilized anti-tumorigenic agents that have been collectively employed as an alternative means of targeting HIF-1α (21). This focus on these inhibitors is due to their shared ability to disrupt the ATP-dependent chaperone activity of HSP90 and block the protein folding of HSP90 client proteins (21).…”
Section: Discussionmentioning
confidence: 99%
“…This focus on these inhibitors is due to their shared ability to disrupt the ATP-dependent chaperone activity of HSP90 and block the protein folding of HSP90 client proteins (21). Previous studies have revealed that the HSP90 inhibitors geldanamycin, 17-AAG and 17-dimethylaminoethylamino-17-demethoxygeldanamycin demonstrate anti-tumorigenic and anti-angiogenic properties in vitro and in vivo in animal models, which is partly due to the ability of these agents to inhibit the function of HIF (22,23).…”
Section: Discussionmentioning
confidence: 99%